2016
DOI: 10.1177/0013916515615389
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling Associations of Neighborhood Street Scale Elements With Physical Activity in Mexican School Children

Abstract: Promoting outdoor play and participation in sports and organized physical activities in children may depend on neighborhood characteristics. This study investigated associations between neighborhood streets and physical activities among Mexican children (N = 1,509, 6-11 years). Child sociodemographic characteristics and physical activity were measured in schools in Guadalajara (n = 10), Mexico City (n = 13), and Puerto Vallarta (n = 3), Mexico, in 2012. Street segments within an 800 m radius around each school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 47 publications
0
32
0
2
Order By: Relevance
“…A study in Chihuahua, Mexico (20), found that among Tarahumara indigenous groups (n = 50), 45% of schoolchildren from 6 -14 years of age spend 4 or more hours in active play per week, and among the Mestizo (n = 61), 27%. A multi-city study of 1 509 children from 6 -11 years of age reported that 76% engage in outdoor play on at least one day per week (21).…”
Section: Organized Sports and Physical Activity Participation:mentioning
confidence: 99%
“…A study in Chihuahua, Mexico (20), found that among Tarahumara indigenous groups (n = 50), 45% of schoolchildren from 6 -14 years of age spend 4 or more hours in active play per week, and among the Mestizo (n = 61), 27%. A multi-city study of 1 509 children from 6 -11 years of age reported that 76% engage in outdoor play on at least one day per week (21).…”
Section: Organized Sports and Physical Activity Participation:mentioning
confidence: 99%
“…One counterintuitive result of our study was that youth living on streets with no litter reported lower neighbourhood-based PA. Few prior studies have isolated the association between specific elements of neighbourhood quality and youth PA, instead relying on composite metrics of objective or parentreported safety (21). The positive relationship between litter and PA observed in this study might beexplained by factors such as mixed land use, increased pedestrian traffic or more population and playmates nearby, which may facilitate greater PA among youth through diverse mechanisms (6,11) but may also result in increased litter and other minor neighbourhood quality issues.…”
Section: Discussionmentioning
confidence: 83%
“…In contrast, one study that incorporated pedestrian environment audits found that objectively measured street‐level characteristics (i.e. the presence of pedestrian amenities and low traffic volume) were positively associated with youth PA in Mexico .…”
Section: Introductionmentioning
confidence: 91%
“…3 A multistate study showed that among 1509 children aged 6 to 11 years, 47% participated in sports and 40% in organized physical activities (eg, dance classes). 31 Regarding competitive sports, the National Youth Olympic Games are held every year in Mexico, where children and youth between 10 and 18 years old from every state in the country compete in 46 sport disciplines. 32 According to reports from CONADE, about 4 million athletes around Mexico participated in the qualifying events, and 25,051 athletes competed in the 2015 games.…”
Section: Organized Sports and Physical Activity Participation: D (4)mentioning
confidence: 99%
“…37 Finally, a multicity study (Guadalajara, Mexico City and Puerto Vallarta) among 1509 children aged 6 to 11 years shows that 76% engage in outdoor play at least 1 day per week. 31 A grade of D-was assigned because, although from small studies employing different definitions of active play, data show that children are not engaging in several hours of active play per day. Echoing previous calls, 38,39 we emphasize the need to promote unstructured, self-directed outdoor play among Mexican children.…”
Section: Active Play: D-(3)mentioning
confidence: 99%